Chemical Profile of Earthworm Flour with Kasgot Media Enriched with Cow Blood and Date Pulp - Ahdavia, Ikrima; Helmi, Imra Atun; Nufus, Hidayati; Farid, Muhammad; Sjahriza, Ahmad (Chimica et Natura Acta, 2025)
Fish meal is used as an ideal protein source for feed with a high level of digestibility but its limited and costly. This study explores earthworm flour as an alternative protein source, cultivated in kasgot (maggot residue) media enriched with organic waste. The novelty of this research lies in using maggot residue as the living medium for earthworms, enhancing the nutritional value of the earthworm flour, making it more beneficial and suitable as an additive protein feed ingredient. The kasgot medium was formulated by mixing boiled cow blood with date pulp fermented with EM4 probiotics in three different ratios: 2:1 (P1), 1:1 (P2), and 1:2 (P3). The gravimetric, Kjeldahl, and Soxhlet were used to measure water, ash, protein, and fat content. High-Performance Liquid Chromatography (HPLC) with post-column derivatization was applied to identify and measure the amino acid level in earthworm flour. Gas Chromatography (GC) was used to analyze fatty acids using the esterification method. The results of the analysis showed that good earthworm flours were P1 and P3. Water, ash, protein, and fat content in P1 were 2.49%, 7.11%, 56.09%, and 18.70%, respectively. Meanwhile, P3 had a water content of 2.87%, ash content of 7.06%, protein of 54.25%, and fat of 23.77%. The highest content of amino acids in P1 was glutamine (7.66 ppm) and lysine (5.37 ppm). The highest content of fatty acids in P3 was oleic acid (13.41%) and palmitic acid (13.37%). These findings suggest that high protein earthworm flour, particularly from P1 formulations, is a promising alternative protein source for animal feed, offering a sustainable and cost-effective solution to the challenges associated with traditional protein sources.